(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2007)
Anfinsen’s thermodynamic hypothesis may be interpreted in two ways: One, that the native 3D structure of the protein, resides in the absolute minimum in the Gibbs energy landscape (GEL). The second, that the Gibbs energy functional, has a single (hence absolute) minimum at the equilibrium distribution of all accessible conformations of the protein. The second is equivalent to the Second Law of Thermodynamics. The first does not follow from the Second Law, and has no theoretical justification. Therefore, the search for an absolute minimum in the Gibbs energy landscape is not necessarily equivalent to a prediction of the native structure of the protein.